LIVER PROFILE CHANGES AMONG MALARIA PARASITE INFECTED PATIENTS - Auta, Timothy; Zakariyya, S.; Everest , A. (FUDMA Journal of Sciences, 2023)
Hepatic dysfunctions are part of the pathological effect of malaria infection among patients. This dysfunction is characterized by increase in liver enzyme activities. In this study, the effect of malaria parasites on liver enzymes among patients attending University Clinic, Federal University Dutsin-Ma, North-Western Nigeria is reported. Blood samples were collected from 118 patients and were examined for parasites using standard methods. Aspartate aminotransferase (AST), Alanine aminotransferase (ALT) and Alkaline phosphatase (ALP) activities were determined using Randox enzymes kits. Out of the 118 examined, 107 (90.68%) were positive for malaria parasites. Prevalence of parasite showed significant association with age groups of patients (P = 0.000), with 6 – 15, 36 – 45, and 46 - 55 years having the highest prevalence of 100% each, while 26 – 35 years had the lowest prevalence of 79.31%. Serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities were significantly higher in the severe group than in the mild and negative groups, with ALT (P = 0.002) and AST (P = 0.02) having significant difference. Only ALT (P = 0.004) had significant difference with age groups of patients. This study revealed very high prevalence of malaria among patients visiting the University Clinic and that malaria infection has effect on hepatic functions, and the level of dysfunction is determined by parasite loads/intensity.